The Effect of Nutrition Education Through Instagram The Four Pillars Of Balanced Nutrition Towards Nutritional Knowledge Of Adolescent Boys at Senior High School In Pontianak Kota District - Elga Miftahul Jannah; Desi Desi; Nopriantini Nopriantini (JOURNAL OF NONCOMMUNICABLE DISEASES, 2021)
Background: Low nutritional knowledge will lead to wrong eating habits so that it can cause nutritional problems in adolescents. Prevention of these nutritional problems requires nutrition education activities with the theme of the four pillars of balanced nutrition through media that can increase adolescent nutrition knowledge. Currently, Instagram is a popular social media among teenagers that can be used as a medium for nutrition education. Based on this, this study was conducted to determine the effect of nutrition education through Instagram with the theme of the four pillars of balanced nutrition on the nutritional knowledge of young men in Pontianak Kota Districts Public High School; Methods: This type of research is a pre-experimental research design with one group pre test – post test. The subjects of the study were male youths of SMA Negeri in Pontianak Kota sub-district, namely SMA N 4 and SMA N 8 Pontianak City. A total of 35 samples were selected by snowball sampling technique. Data collection techniques through a rolling process from one respondent to another to meet the needs of researchers. The data were analyzed using the Wilcoxon Test to see the difference in nutritional knowledge before and after being given nutrition education;  Results: obtained a p value (p-value) of 0.000, which means that there is a difference before and after being given nutritional intervention in the form of nutrition education on the nutritional knowledge of high school boys in Pontianak Kota District; Conclusions: Nutrition education through Instagram with the theme of the Four Pillars of Balanced Nutrition can increase adolescent nutrition knowledge.